Vibrational hierarchy leads to dual-phonon transport in low thermal conductivity crystals - Yixiu Luo (Nature Portfolio, 2020)
Predicting thermal transport in low-thermal-conductivity (κ L) materials is challenging. Here, the authors propose a dual-phonon theory, where normal phonons are treated using the Boltzmann thermal equation and diffuson-like phonons are treated within diffusion theory, yielding robust predictions of κ L.